MAZIKO - Malawi integrated maternal and child grant project - Roschnick, Natalie (Save the Children, 2023)
MAZIKO (meaning “Foundation” in Chichewa), is a 5-year project that integrates maternal and child grants (cash transfers) with a package of government recommended social and behaviour change and capacity strengthening interventions to improve child nutrition and development. The project was launched in November 2021 and is reaching nearly 42,000 households with pregnant women and children under 5 years, in Ntcheu and Balaka districts in Malawi. It includes a large research component, including a cluster randomized trial to evaluate the impact, cost effectiveness, and scalability of maternal and child grants, delivered alongside an integrated multi-sector social and behaviour change intervention package to address the main drivers of malnutrition. The evidence generated will inform Malawi’s National Social Protection system, and guide improvements to the delivery of Malawi’s multi-sector nutrition strategy.